Examining the Relationship Between Gamification-Based Quizizz Use and English Vocabulary Mastery in Elementary Education - Zahratul munawarah; Hijrah Syam; Abdul Gafur Marzuki (Sakura Digital Nusantara, 2026)
This study was conducted in response to the growing integration of information and communication technology in English language learning, which has created opportunities to enhance students’ vocabulary acquisition through more interactive and engaging instructional media. Vocabulary mastery is a fundamental component of English proficiency, yet many elementary school students continue to experience difficulties in learning new vocabulary through conventional teacher-centered approaches. Therefore, this study aimed to examine the relationship between the use of gamification-based Quizizz and English vocabulary mastery among sixth-grade students at MIN 1 Kota Palu. A quantitative correlational research design was employed, involving 30 students selected through purposive sampling from a population of 63 students. Data were collected using a 15-item Likert-scale questionnaire measuring students’ use of Quizizz and a 20-item multiple-choice vocabulary test. The data were analyzed using IBM SPSS Statistics version 30 through normality, linearity, and Pearson Product Moment correlation tests. The findings indicated that the data satisfied the assumptions of normality and linearity. Pearson correlation analysis revealed a very strong positive and statistically significant relationship between Quizizz use and students’ English vocabulary mastery (r = .892, p < .001), indicating that greater engagement with Quizizz was associated with higher vocabulary achievement. The study concludes that Quizizz has considerable potential as a gamification-based learning medium to foster engaging, interactive, and student-centered vocabulary learning in elementary English classrooms. However, because the study employed a correlational design, the findings demonstrate an association rather than a causal effect between Quizizz use and vocabulary mastery.